The causal impact of saturated fatty acids on rheumatoid arthritis: a bidirectional Mendelian randomisation study - Yao, Xiaoling; Yang, Yuzheng; Jiang, Zong; Ma, Wukai; Yao, Xueming (Frontiers in Nutrition, 2024)
Objective: The causal relationship between saturated fatty acids (SFAs) and rheumatoid arthritis (RA) remains poorly understood. This study aimed to determine whether SFAs are causally related to RA using Mendelian randomisation (MR) analyses. Methods: Genome-wide association study (GWAS) summary data for RA (ukb-d-M13_RHEUMA) and SFAs (met-d-SFA) were obtained from the Integrative Epidemiology Unit OpenGWAS database. A bidirectional MR analysis was performed using a suite of algorithms, namely the MR-Egger, weighted median, simple mode, weighted mode, and inverse variance weighted (IVW) algorithms, all integrated using the ‘MR’ function. The robustness of the MR findings was further evaluated through sensitivity analyses, including heterogeneity, horizontal pleiotropy, and leave-one-out tests. Results: The IVW algorithm in the forward MR analysis indicated a causal link between SFAs and RA (p = 0.025), identifying SFAs as a risk factor for RA (odds ratio = 1.001). Sensitivity analyses indicated no significant heterogeneity, horizontal pleiotropy, or severe bias, reinforcing the credibility of the forward MR results. However, the reverse MR analysis revealed that RA does not causally affect SFA levels (p = 0.195), and this finding was supported by corresponding sensitivity analyses. Conclusion: The findings of this study substantiate the positive causal effect of SFAs on the incidence of RA through bidirectional MR analysis, thereby offering a consequential direction for future research on the diagnosis and treatment of RA.